The Mediating Role of Satisfaction with Life and Social Interaction Anxiety in the Relationship Between Loneliness and Regulatory Emotional Self-Efficacy - Juncheng Guo; Mansor Abu Talib; Bolin Guo; Jiaxin Ren; Jia Liu (Behavioral Sciences)
Regulatory emotional self-efficacy represents individuals’ belief in their capacity to manage emotions effectively and plays a vital role in supporting emotional well-being and adaptive functioning, particularly in university students. This study explores the influence of loneliness on regulatory emotional self-efficacy and its underlying mechanisms by incorporating two mediating variables—satisfaction with life and social interaction anxiety—within a chain mediation model. A total of 547 undergraduate students from a university located in Nanchang, Jiangxi Province, participated in the survey. The findings reveal that loneliness directly impacts regulatory emotional self-efficacy; satisfaction with life mediates the effect of loneliness on regulatory emotional self-efficacy; social interaction anxiety also mediates the effect of loneliness on regulatory emotional self-efficacy; and satisfaction with life and social interaction anxiety jointly serve as chain mediators in the relationship between loneliness and regulatory emotional self-efficacy. This study sheds light on the connection between loneliness and regulatory emotional self-efficacy, offering a theoretical basis and practical guidance for improving students’ emotional regulation and overall well-being.